Underutilization of Endovascular Therapy in Black Patients With Ischemic Stroke: An Analysis of State and Nationwide Cohorts. Issue 3 (24th January 2022) - Kim, Youngran; Sharrief, Anjail; Kwak, Min Ji; Khose, Swapnil; Abdelkhaleq, Rania; Salazar-Marioni, Sergio; Zhang, Guo-Qiang; Sheth, Sunil A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Endovascular therapy (EVT) is a very effective treatment but relies on specialized capabilities that are not available in every hospital where acute ischemic stroke is treated. Here, we assess whether access to and utilization of this therapy has extended uniformly across racial and ethnic groups. Methods: We conducted a retrospective, population-based study using the 2019 Texas Inpatient Public Use Data File. Acute ischemic stroke cases and EVT use were identified using the International Classification of Diseases, Tenth Revision (ICD-10 ) diagnosis and procedure codes. We examined EVT utilization by race/ethnicity and performed patient- and hospital-level analyses. To validate state-specific findings, we conducted patient-level analyses using the 2017 National Inpatient Sample for national estimates. To assess independent associations between race/ethnicity and EVT, multivariable modified Poisson regressions were fitted and adjusted relative risks were estimated accounting for patient risk factors and socioeconomic characteristics. Results: Among 40 814 acute ischemic stroke cases in Texas in 2019, 54% were White, 17% Black, and 21% Hispanic. Black patients had similar admissions to EVT-performing hospitals and greater admissions to comprehensive stroke centers (CSCs) compared with White patients (EVT 62% versus 62%, P =0.21; CSCs 45% versus 39%, P <0.001) but had lower EVT rates (4.1% versus 5.3%; adjusted relative risk, 0.76 [0.66–0.88]; P <0.001). There were no differences in EVT rates between Hispanic and White patients. Lower rates of EVT among Black patients were consistent in the subgroup of patients who arrived in early time windows and received intravenous recombinant tissue-type plasminogen activator (adjusted relative risk, 0.77 [0.61–0.98]; P =0.032) and the subgroup of those admitted to EVT-performing hospitals in both non-CSC (3.0% versus 5.5, P <0.001) and CSC hospitals (7.9% versus 10.4%, P <0.001) while there were no differences between Whites and Hispanic patients. Nationwide sample data confirmed this finding of lower utilization of EVT among Black patients (adjusted relative risk, 0.87 [0.77–0.98]; P =0.024). Conclusions: We found no evidence of disparity in presentation to EVT-performing hospitals or CSCs; however, lower rates of EVT were observed in Black patients.